Pengaruh orientasi kewirausahaan dan modal sosial terhadap keberlanjutan usaha UMK kuliner di Kota Malang dengan kemampuan inovasi sebagai intervening - Dewi , Ayu Putriana; Suharsono, Naswan; Churiyah, Madziatul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of entrepreneurial orientation and social capital on the sustainability of culinary MSMEs in Malang City, with innovation capability as a mediating variable. Using a quantitative approach and purposive sampling, data were collected from 373 respondents and analyzed using PLS-SEM. The results show that entrepreneurial orientation and social capital significantly affect innovation capability and business sustainability, both directly and indirectly. Innovation capability partially mediates these relationships. The findings imply that strengthening innovation, adaptability, and social networks is essential for enhancing the long-term sustainability of culinary MSMEs in dynamic market conditions. Keywords: Entrepreneurial orientation; Social capital; Innovation capability; Business sustainability; Culinary MSMEs; Dynamic capabilities; PLS-SEM